2017
DOI: 10.1186/s40691-017-0091-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing consumers’ purchase intention of green sportswear

Abstract: The purpose of this study was to examine consumers’ purchase intention for green sportswear by investigating the effects of their expectation, perception, subjective norm, perceived behavior control, and attitude on purchasing green sportswear. The study further investigated differential influences towards purchase intention for green sportswear between non-green and green product users. A within-subjects research design was used to empirically test our conceptual model, which was expanded from the theory of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
124
3
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(159 citation statements)
references
References 47 publications
(39 reference statements)
26
124
3
6
Order By: Relevance
“…Therefore, H5 is also accepted. This finding is consistent with the findings of many other researchers including Nam, Dong, & Lee., (2017); Giampietria at al. (2018);and Rehman, Bhatti, Mohamed, & Ayoup (2019).…”
Section: Relationship Between Trust and Consumer Intentionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, H5 is also accepted. This finding is consistent with the findings of many other researchers including Nam, Dong, & Lee., (2017); Giampietria at al. (2018);and Rehman, Bhatti, Mohamed, & Ayoup (2019).…”
Section: Relationship Between Trust and Consumer Intentionsupporting
confidence: 93%
“…Accordingly, H9 is rejected. This finding is consistent with the finding of Chai and Pavlou (2004) and Nam, Dong, and Lee (2017). There can be several reasons behind the non-significant relationship found here.…”
Section: Relationship Between Perceived Behaviour Control and Intentionsupporting
confidence: 93%
See 1 more Smart Citation
“…Findings from apparel research that incorporates TPB have shown that attitude [24,27,28], injunctive (or subjective) norms [24,[27][28][29], and descriptive norms [24,29] have significant effects on American consumers' intentions to purchase green apparel. There are significantly less studies that examine consumers from other countries, however, one study found that the strongest predictor of intentions to purchase green apparel among Chinese consumers was attitude followed by PBC and injunctive norms [30].…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Consumer's desire to buy green products (green purchase intention) is influenced by several factors such as personal norms, subjective norms, attitude, perceived behavioral control and perception (Nam et al, 2017;Khare, 2015). Purchasing behavior towards green products is the tendency of consumers to buy eco-friendly products that are influenced by attitude, personal norms and willingness to pay.…”
Section: Green Purchase Behaviormentioning
confidence: 99%